A philosophy of havruta : understanding and teaching the art of text study in pairs - Holzer, Elie; Kent, Orit (Jewish identities in post modern society., 2013)
No longer confined to traditional institutions devoted to Talmudic studies, havruta work, or the practice of students studying materials in pairs, has become a relatively widespread phenomenon across denominational and educational settings of Jewish learning. However, until now there has been little discussion of what havruta text study entails and how it might be conceptualized and taught. This book breaks new ground from two perspectives: by offering a model of havruta text study situated in broader theories of interpretation and learning, and by treating havruta text study as composed of textual, interpersonal and intra-personal practices which can be taught and learned. We lay out the conceptual foundations of our approach and provide examples of their pedagogical implementation for the teaching of havruta text study. Included are illustrative lesson plans, teachers' notes and students' reflections, exercises for students, and other instructional materials for teaching core concepts and practices.